The Impact of Positioning Strategy on Customer Selection: A Case Study of BRI, BNI, and Mandiri Banks Using Multidimensional Scaling (MDS) - Anggraini, Galih Arum (Proceeding of International Management Conference and Progressive Papers, 2024)
The banking industry in Indonesia is growing rapidly along with increasing competition and digitalization of financial services. This study aims to analyze customer perceptions of banking product attributes offered by BRI, BNI, and Mandiri in Ngawi Regency. The method used is descriptive quantitative with Multidimensional Scaling (MDS) analysis technique. Data was collected from 60 customers through a Likert-scale questionnaire assessing attributes such as service quality, security, information availability, price, accessibility, and technological innovation. The results of the analysis show that BRI excels in security services, Mandiri is perceived as strong in information availability, while BNI excels in price, accessibility and technological innovation. No bank specifically excels in service quality. Each bank has different advantages according to customer perception, which can be the basis for designing a more effective positioning strategy.